Psychological Aspects Of Improving Women's Professional Skills - Tokhirova Guzaloy (Zien Journals, 2024)
In this article, on the path of professional development of women in our country, more favorable conditions are created for their quality education. Today, supporting the scientific potential and qualifications of our women, in a word, the systematic formation of a professional career, is illuminated from a scientific point of view. It is based on the need to reform practical work on shaping the professional careers of women and girls and their development during professional activities, as well as ensuring their advancement through the ranks.
Keywords: Support for women; family institution; socio-economic life